Effect of nutrients with GA3 and residual effect of rice residue, FYM and nutrients applied to preceding potato on growth, yield and quality ofwheat (Triticum aestivum) in rice (Oryza sativa)-potato (Solanum tuberosum)–wheat cropping system - NOORI, NOORIALI; MANHAS, S S; SHARMA, VIVEK; SINGH, SOMPAL (The Indian Journal of Agricultural Sciences, 2025)
A field experiment was conducted during winter (rabi) and rainy (kharif) season of 2020–21 and 2021–22 at Punjab Agricultural University, Ludhiana, Punjab to enhance the productivity of wheat (Triticum aestivum L.) in rice (Oryza sativa L.)-potato (Solanum tuberosum L.)-wheat cropping system. The experiment was laid out in factorial randomized block design (F-RBD) with two factors, Factor A [Two nutrient management treatments (rice straw incorporation + 100 RDF + FYM @25 t/ha and without rice straw incorporation + 100 RDF + FYM @50 t/ha)] and Factor B [Nine nutrient with GA3 treatments (75% recommended N and P, 75% recommended N, 50% recommended N and P, 50 % recommended N, 200 ppm gibberellic acid (seed treatment) + 75% recommended N and P, 200 ppm gibberellic acid (seed treatment) + 75% recommended N, 100 ppm gibberellic acid (seed treatment) + 50% recommended N and P, 100 ppm gibberellic acid (seed treatment) + 50% recommended N and water soaking (seed treatment) + 50% recommended N]. Application of FYM @50 t/ha + 100 RDF without rice residue to preceding potato crop showed significant improvement on growth character, viz. plant height, tillers and dry matter accumulation of succeeding wheat crop as compared to rice straw incorporation (RSI) + 100 RDF + FYM @25 t/ha during both the year. Similarly application of FYM @50 t/ha +100 RDF without rice residue to preceding potato crop showed significant maximum yield attributing characters and yield of succeeding wheat crop during both the year.The application of no rice residue with FYM @50 t/ha +100% RDF recorded 12.8 and 14.9% increased grain yield of wheat than rice straw incorporation (RSI) + 100% RDF + FYM @25 t/ha during first and second year of experimentation, respectively.The application of GA3 irrespective of nutrients levels increased the germination percentage significantly as compared to no GA3 application treatments at 10 and 12 DAS during both the years. The application of GA3 advanced the germination by 2 days as compared to no GA3 application. The maximum growth, yield attributing character andyield in wheat recorded with 75% RDN and P + GA3 @200 ppm which at par with GA3 @200 ppm + 75% RDN, GA3 @100 ppm + 50% RDN and P, 75% RDN and P, 75% RDN and 50% RDN and P while significantly higher than other treatments during both the years.